Progress and Challenges in Precise Treatment of Tumors With PD-1/PD-L1 Blockade - Jiang, Youhai; Zhao, Xiaofang; Fu, Jing; Wang, Hongyang (Frontiers in Immunology, 2020)
Immune checkpoint inhibitor (ICI) treatment targets inhibitory receptors on T cells to release antitumor ability achieved significant antitumor efficacy in treating various cancers, especially hematological tumors. However, due to tumor heterogeneity and individual patient differences, the patient ORR (overall response rate) of PD-1/PD-L1 blockade is only 20%-30%, its response rate in solid tumors is relatively low and serious side effects are seen in some patients. There are still many unknown factors affecting the therapeutic effect of PD-1/PD-L1 blockade. How to accurately and effectively screen responding tumor patients and explore how to improve patients’ response rate and efficacy, is a huge challenge for the precise treatment of tumors. Here we attempt to summarize the recent progress in response prediction, combined application of PD-1/PD-L1 blockade therapy and side effects, and briefly discuss the methods and evaluations combined with PD-1/PD-L1 blockade to improve the implementation of precision immunotherapy.